2007
DOI: 10.1667/rr0962.1
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Efaproxyn™ (Efaproxiral) on Subcutaneous RIF-1 Tumor Oxygenation and Enhancement of Radiotherapy-Mediated Inhibition of Tumor Growth in Mice

Abstract: Efaproxiral, an allosteric modifier of hemoglobin, reduces hemoglobin-oxygen binding affinity, facilitating oxygen release from hemoglobin, which is likely to increase tissue pO(2). The purpose of this study was to determine the effect of efaproxiral on tumor oxygenation and growth inhibition of RIF-1 tumors that received X radiation (4 Gy) plus oxygen breathing compared to radiation plus oxygen plus efaproxiral daily for 5 days. Two lithium phthalocyanine (LiPc) deposits were implanted in RIF-1 tumors in C3H … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
40
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 30 publications
(44 citation statements)
references
References 37 publications
4
40
0
Order By: Relevance
“…These AEHs have potential therapeutic applications in treating ischemia-related cardiovascular diseases, such as angina, myocardial ischemia, stroke, trauma, where more O 2 is needed to heal tissue or organs. 5459 A second class of AEHs, which includes several aromatic aldehydes, on the contrary, bind to Hb to increase its O 2 affinity by preferentially stabilizing the R-state relative to the T-state (Fig. 2B).…”
Section: Hemoglobin – a Target For Drug Designmentioning
confidence: 99%
“…These AEHs have potential therapeutic applications in treating ischemia-related cardiovascular diseases, such as angina, myocardial ischemia, stroke, trauma, where more O 2 is needed to heal tissue or organs. 5459 A second class of AEHs, which includes several aromatic aldehydes, on the contrary, bind to Hb to increase its O 2 affinity by preferentially stabilizing the R-state relative to the T-state (Fig. 2B).…”
Section: Hemoglobin – a Target For Drug Designmentioning
confidence: 99%
“…25-28 Right-shifters encompass both covalent binders, such as aromatic aldehydes, 29,30 and non-covalent binders, e.g. aromatic propionates.…”
Section: Introductionmentioning
confidence: 99%
“…Once introduced in the tissue of interest, they allow repeated measurement of pO 2 at the same site for up to years after implantation. Based on extensive pre-clinical and some clinical studies [2630], EPR oximetry with particulate paramagnetic materials has shown several advantages, especially for the repetitive and accurate measurement of localized tissue pO 2 . However, these studies have also indicated the areas in which progress is needed, particularly the need for technological developments that can enable measurements in tissues at depths of greater than 10 mm.…”
Section: Introductionmentioning
confidence: 99%